Rapid injection of lumbar dorsal root ganglia under direct vision: Relevant anatomy, protocol, and behaviors - Yuan, Xiaoman; Han, Siyi; Zhao, Fengtian; Manyande, Anne; Gao, Feng; Wang, Jie; Zhang, Wen; Tian, Xuebi (Frontiers in Neurology, 2023)
Introduction Dorsal root ganglia (DRG) are anatomically well-defined structures that contain all primary sensory neurons and are distension nodules of the dorsal root in the spinal cord near the medial surface of each foramen. Therefore, DRG is considered to be a desirable target for injection to manage chronic pain. But it presents a limitation in probing deep into it without in vivo injection technology. Methods Here, we described a technique for administering intraganglionic injections of lumbar DRG under direct vision. We use partial osteotomy rather than laminectomy, which removes more bone, to preserve spinal structures while gaining adequate DRG access. To monitor the intraoperative progress of the DRG injection, a non-toxic dye was utilized. The effectiveness of the injection on the diffusion of AAV (adeno-associated virus) within the ganglion was assessed by histopathology at postoperative day 21. Results Behavioral tests showed that neither motor nor sensory abilities were affected by saline or AAV injections. Meanwhile, the decreased pain threshold of SNI (spared nerve injury) was considerably restored by pharmacological inhibition of DRG neurons. Discussion Our research achieved a new minimally invasive and intuitive intra-ganglionic injection in mice. In addition, the present protocol may serve as a valuable resource for planning preclinical studies of DRG injection.